A Comparative Analysis of the Russian – Ukrainian war coverage on Arabic News Websites: Al Jazeera Net vs. Al Arabiya Net in 2025 - Teniou, Soumia; Fadhloune, Amel; Bouanane, Asma; Madoui, Meryem (Київський національний університет імені Тараса Шевченка, 2025)
This article examines trends in the coverage of the Russia-Ukraine war on two Arabic websites, Al Jazeera and Al Arabiya, three years after its start. The study aims to achieve the following objectives: to analyze and quantify the media content related to the war on these two major Arabic news websites, and to conduct a comparative analysis of the media content on both news websites, focusing on themes, issues, and coverage trends. Method. To analyze and quantify media content published on the Al Jazeera and Al Arabiya websites, specifically issues and trends, content analysis was utilized to research 99 pieces of media content from both websites published between February 24, 2025, and June 24, 2025. Results. It was observed that both websites primarily focused on the political topics of the war; secondly, both websites demonstrated an emphasis on the military aspect. The humanitarian sphere ranked third, while the economic coverage was relatively low. Both websites demonstrated a shared trend of portraying Ukraine in a more favorable light while framing Russia more negatively. However, the degree of intensity and editorial framing between the two media differed. Conclusion. Both websites engaged with various issues of the Russia-Ukraine war, including political, military, humanitarian, social, and economic issues, with different levels of attention. The coverage by both Al Jazeera and Al Arabiya of the Russia-Ukraine war was generally objective to some extent. However, a thorough analysis of the coverage trends indicates a slight bias favoring the Ukrainian perspective.

У цій статті розглядаються тенденції висвітлення російсько-української війни на двох арабських веб-сайтах, Al Jazeera та Al Arabiya, через три роки після її початку. Дослідження має на меті досягти таких цілей: проаналізувати та кількісно оцінити медіаконтент, пов'язаний з війною, на цих двох основних арабських новинних веб-сайтах, а також провести порівняльний аналіз медіаконтенту на обох новинних веб-сайтах, зосереджуючись на темах, проблемах та тенденціях висвітлення. Метод. Для аналізу та кількісної оцінки медіаконтенту, опублікованого на веб-сайтах Al Jazeera та Al Arabiya, було використано контент-аналіз для дослідження 99 медіаконтентів з обох веб-сайтів, опублікованих у період з 24 лютого 2025 року по 24 червня 2025 року. Результати. Було помічено, що обидва веб-сайти в основному зосереджувалися на політичних темах війни; по-друге, обидва веб-сайти продемонстрували акцент на військовому аспекті. Гуманітарна сфера посіла третє місце, тоді як економічне висвітлення було відносно низьким. Обидва веб-сайти продемонстрували спільну тенденцію зображувати Україну в більш сприятливому світлі, одночасно зображуючи Росію більш негативно. Однак ступінь інтенсивності та редакційне фреймування між двома ЗМІ відрізнялися. Висновки. Обидва вебсайти займалися різними питаннями російсько-української війни, включаючи політичні, військові, гуманітарні, соціальні та економічні, з різним рівнем уваги. Висвітлення російсько-української війни як Al Jazeera, так і Al Arabiya було загалом певною мірою об'єктивним. Однак ретельний аналіз тенденцій висвітлення свідчить про незначну упередженість на користь української точки зору.
Порівняльний аналіз висвітлення російсько-української війни на арабських новинних сайтах у 2025 році: Al Jazeera проти Al Arabiya
Keywords: Russia-Ukraine war; Al Jazeera; Al Arabiya; issues; trends; media and mass communication; російсько-українська війна; Аль-Джазіра; Аль-Арабія; проблеми; тенденції; медіа і масова комунікація